2011
DOI: 10.1364/oe.19.000a72
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of aerosol extinction-to-backscatter ratios by combining ground-based and space-borne lidar elastic scattering measurements

Abstract: A technique to determine the aerosol extinction-to-backscatter ratio (lidar ratio) as well as extinction and backscatter coefficients from simultaneous ground-based and space-borne lidar measurements is proposed. This technique can be applied in presence of more than one aerosol layer. To test the reliability of this technique, a numerical simulation has been performed. Moreover, the technique has been applied to an actual case by analyzing data from Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Raman lidar systems are now widely used for profiling vertical distributions of aerosol in the atmosphere (Amiridis et al, 2011;Groß et al;Lu et al, 2011). Depending on the sophistication of the instrument the shape and microphysics of aerosol particles can be established.…”
Section: Introductionmentioning
confidence: 99%
“…Raman lidar systems are now widely used for profiling vertical distributions of aerosol in the atmosphere (Amiridis et al, 2011;Groß et al;Lu et al, 2011). Depending on the sophistication of the instrument the shape and microphysics of aerosol particles can be established.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (e.g., Tao et al, 2008;Lu et al, 2011;Ferrare et al, 2001;Müller et al, 2007;Haarig et al, 2016) investigated the LR for different atmospheric conditions and aerosol types, like dust in Groß et al (2011) and volcanic ash in Ansmann et al (2010). The studies showed that the LR is a highly variable parameter depending on the predominant aerosol.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%
“…The dynamic shape factor is represented by χ. In this study we assumed an effective aerosol particle density of 1.6 g cm −3 , according to Ma et al (2014), for the fine-mode aerosol. The effective density combines the particle density and dynamic shape factor.…”
Section: Particle Number Size Distributionmentioning
confidence: 99%
“…The mixing state can be assumed by different mixing approaches. The dry-state optical closure study by Ma et al (2014) shows that the approach of internally mixed coated (aerosol particles consists of a core surrounded by a shell; core-shell approach) aerosol particles results in the best agreement between modeled and measured hemispheric backscatter coefficients for Melpitz. Furthermore, Zhang and Thompson (2014) and Kahnert et al (2012) discussed the mixing morphology and its influence on particle light absorption and scattering.…”
Section: Airborne In Situ Aerosol Optical Propertiesmentioning
confidence: 99%